2019
DOI: 10.9734/ajess/2019/v4i330121
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Peer Tutoring on Seventh-grade Students’ Learning in Science

Abstract: Peer tutoring is a common instructional strategy used in classrooms. This study focused on the effects that peer tutoring has on students of the novice group. The effect of peer tutoring was compared based on the score of pretest and posttest to those of the control group. At the end of the tutoring session, the satisfaction of the students was accessed by administering questionnaires. Hence, this is a mix-mode research where survey questionnaire and class tests score has been used. The questionnaires consist … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
1
1
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…However, the instructors reported that the activity involved a substantial time commitment and that they lacked sufficient technological support and would have valued professional development related to the activity. Overall, studies have found more benefits than drawbacks from implementing peer teaching in the classroom, including improved student participation (Sansone et al, 2018), positive attitudes, higher levels of learning satisfaction (Ghalley et., 2019), and improved learning (Made et al, 2020).…”
Section: Collaborationmentioning
confidence: 99%
“…However, the instructors reported that the activity involved a substantial time commitment and that they lacked sufficient technological support and would have valued professional development related to the activity. Overall, studies have found more benefits than drawbacks from implementing peer teaching in the classroom, including improved student participation (Sansone et al, 2018), positive attitudes, higher levels of learning satisfaction (Ghalley et., 2019), and improved learning (Made et al, 2020).…”
Section: Collaborationmentioning
confidence: 99%
“…Lecturers can apply the peer tutor strategy for students in blended learning with technological devices. In addition, the peer tutor strategy also has many benefits such as a positive attitude and level of learning satisfaction [21], success in learning [22], or learning outcomes [23], and student participation [24]. Therefore, integrated blended learning with peer tutors is the most appropriate alternative for implementing new normal era learning at the college level Teaching for learning and learning to teaching focuses on the quality of teaching in higher education.…”
Section: Introductionmentioning
confidence: 99%
“…Not all peer tutors are "experts". They are sometimes [27]. In peer tutor, students generally identify more easily than with older (teachers/lecturers), and this helps create an environment where students are more comfortable to ask questions and work through challenging problems in a free-form classroom environment [28].…”
Section: Introductionmentioning
confidence: 99%